PENGARUH KOMPENSASI, KEPUASAN KERJA DAN PENGEMBANGAN KARIR TERHADAP RETENSI KARYAWAN DI KUTABEX HOTEL - Aditeresna, Kadek Arya Reta; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p01, 2018)
The purpose of this study is to explain the effect of compensation, job satisfaction and career development on employee retention. This research was conducted in Kutabex Hotel involving 68 employees through saturated sample method and data collection was done by observation, interview and questionnaires. Data analysis technique used is multiple linier regression . The results of this study found that the compensation, job satisfactio n and career development have a positive and significant impact on employee retention . The hotel should be able to provide fair compensation to employees to increase employee retention. Job satisfaction is important to note because when employees feel satisfied with their work it will increase the retention rate. Can pay attention to the careers of its employees also have an important role to be able to increase retention.   Keywords :com pensation , job satisfaction, career development, employee retention.